Time, Space and Subaltern Phenomenology in the Documentary Film Essay Taste of Cement - Naeff, Judith (FRAME, Journal of Literary Studies, 2026)
This article analyses how the film essay Taste of Cement by Ziad Kalthoum portrays Syrian construction labourers in Lebanon. It shows that the film’s evocation of sensory experience makes two important contributions to the way we conceive of cities in general, and of post-civil war Beirut in particular. First, Taste of Cement succeeds in representing the workers as subaltern subjects without participating in their erasure. Second, the film presents a view that I call “oscillating urbanism,” thus challenging conventional narratives of (post-)conflict cities.